O papel da ultrassonografia transvaginal tridimensional como fator preditivo da receptividade endometrial na fertilização in vitro - Borges, Layza Merizio [UNIFESP] (2016)
Introduction: A favorable endometrial environment is extremely important to the success of in vitro fertilization (IVF) cycles, and endometrial receptivity has a relative contribution of 31-64% for pregnancy. What determines such receptivity, however, remains controversial. Objectives: To evaluate the application of three-dimensional ultrasound with power Doppler angiography (3D US) in endometrial parameters, volume and vascularization, in women undergoing IVF cycles with embryo fresh and after vitrified-warmed transfer, and compare them to traditional parameters used in two-dimensional ultrasonography (2D US), endometrial thickness and aspect, as new pregnancy predictors. Methods: An observational, longitudinal and prospective study including 181 women undergoing ovarian stimulation standard protocols and endometrial preparation in private clinic of assisted reproduction, between 2012 and 2015. The participants were divided into two groups, according to the embryo transfer protocol: IVF with fresh embryo transfer (IVF-ET) (n = 123) and IVF with vitrified-warmed embryo transfer (IVF-CET) (n = 58). All patients underwent 2D US to measure endometrial thickness and 3D US for evaluating the endometrial volume and vascularization (VI, FI, VFI) on the day of hCG administration or after hormonal preparation of the endometrium. All examinations were performed by the same professional using the equipment ACCUVIX XQ (Medison, Seoul, South Korea). The VOCAL® instrument was the imaging program used to calculate the endometrial volume and vascularization, traced in 12 plans to cover 180 °. The IVF-ET and IVFCET groups were divided into two subgroups, according to the clinical outcome of treatment: pregnancy and non-pregnancy. The variables were compared between groups, and a multivariate logistic regression model was used to evaluate the association of ultrasound variables on the outcome of clinical pregnancy. Results: In IVF-ET group, the pregnancy rate was 31.7%. The multiple logistic regression analysis showed that endometrial volume was predictive factor of pregnancy (OR 1.41, p = 0.003), increasing pregnancy rate of 40%, while the endometrial thickness was a weak predictor of pregnancy (OR: 1.20, p = 0.05), after adjusting for the confounding factors such as age, antral follicle count, FSH dose, number of MII oocytes and number of higher grade of embryos transferred. The ROC curve analysis showed that an endometrial volume of 2.0 cm3 is a pregnancy predictor (p = 0.002), with a sensitivity of 95% and specificity of 82%. In IVF-CET group, the pregnancy rate was 22.4% and there was no positive association between endometrial volume and thickness with pregnancy rate statistically significant. The parameters of endometrial vascularization (VI, FI and VFI) did not constitute predictors of pregnancy in both groups. Conclusions: The endometrial volume exceeding 2.0 cm3, as measured by US 3D, is a predictive factor of pregnancy in IVF-ET cycles, increasing in 40% pregnancy rate and this method is applicable in assisted reproduction cycles, with low variability interobserver.